2016
DOI: 10.3389/fnagi.2016.00167
|View full text |Cite
|
Sign up to set email alerts
|

Upper-Extremity Dual-Task Function: An Innovative Method to Assess Cognitive Impairment in Older Adults

Abstract: Background: Difficulties in orchestrating simultaneous tasks (i.e., dual-tasking) have been associated with cognitive impairments in older adults. Gait tests have been commonly used as the motor task component for dual-task assessments; however, many older adults have mobility impairments or there is a lack of space in busy clinical settings. We assessed an upper-extremity function (UEF) test as an alternative motor task to study the dual-task motor performance in older adults.Methods: Older adults (≥65 years)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
70
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 72 publications
8
70
0
1
Order By: Relevance
“…Consequently, the addition of a cognitive oriented task resulted in worse performance compared to the addition of a motor oriented task, similarly to previous studies (Brustio et al, 2020;Ghai et al, 2017;Woollacott and Shumway-Cook, 2002). Similar findings were also provided regarding DT conditions proposed involving the upper extremities (Toosizadeh et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Consequently, the addition of a cognitive oriented task resulted in worse performance compared to the addition of a motor oriented task, similarly to previous studies (Brustio et al, 2020;Ghai et al, 2017;Woollacott and Shumway-Cook, 2002). Similar findings were also provided regarding DT conditions proposed involving the upper extremities (Toosizadeh et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
“…Our results obtained in DT condition, even if a postural balance task was not involved, are similar to those previously described. Indeed, a correlation exists between upper and lower extremities movements (Fraser et al, 2010), also in a DT setting (Toosizadeh et al, 2016) meaning that the cognitive processes involved are similar.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for a contraction with the cognitive challenge, maximal strength did not improve the model to predict CV of force compared with age of the individual or Trail-making-Test results in young or older adults (step 1 in Tables 2 , 3 ). The findings of age and sex-related differences in CV of force during a cognitive challenge task expand previous observations of impaired motor function during several motor tasks of the upper extremity such as dexterity tests, finger tapping tasks and reaction time tests in young and older adults ( Zijdewind et al, 2006 ; Fraser et al, 2010 ; Toosizadeh et al, 2016 ). Physiological mechanisms driving the differences in motor performance during cognitive challenging tasks in men and women are not fully understood, but alterations in cognitive function with aging may partly explain these findings as discussed below.…”
Section: Discussionsupporting
confidence: 83%
“…Vibration of muscle can cause some illusionary sensation in the brain regarding the lower-extremity position [ 8 , 11 ]. Previous studies showed deterioration in position and motion sensing of muscle spindles with aging [ 11 , 30 ], and aging-induced alterations in central nervous system, such as decreased attentional resources and a general loss of neural substrate [ 31 , 32 ]. Therefore, it has been hypothesized here that vibration would cause less illusionary disturbance within central nervous system among elders with impaired balance since messages from spindle units are weaker and the central nervous system may be less sensitive to the disturbance of these messages.…”
Section: Discussionmentioning
confidence: 99%